USM AIMS FOR THE PRESERVATION AND CONSERVATION OF LOCAL KNOWLEDGE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
BANDUNG, 14 October 2015 – Preservation and conservation of the local indigenous knowledge, which is facing erosion due to modernisation, has become a priority for Universiti Sains Malaysia (USM) to benefit future generations, and is currently being implemented via collaborations with various authorities.